A large two-centre study in to rates of influenza and pneumococcal vaccination and infection burden in rheumatoid arthritis in the UK. Issue 1 (December 2016) - Subesinghe, Sujith; Rutherford, Andrew; Ibrahim, Fowzia; Harris, Helen; Galloway, James
Abstract Background Infections are a common complication of RA with associated morbidity and mortality. The aetiology of increased risk is complex and multifactorial. Despite this, strategies to mitigate against risk of infection including vaccination are not always addressed in primary or secondary care with wide variation in practice from multiple small single centre audits. This study was a large two-centre survey of vaccine uptake in routine clinical practice and evaluated the relationship between vaccination and the burden of infection in RA patients. Methods A patient questionnaire was devised and disseminated through postal, clinic and phone survey at 2 UK rheumatology centres, detailing past vaccination history, reasons for non-vaccination, and history of recent infection. In a subset of patients, primary care vaccination data were also obtained. Results In total 929 patients responded to the survey. Over 85 % of patients were vaccinated against influenza, however only 44 % were vaccinated against pneumococcus. The vast majority of vaccination was undertaken in primary care. In the 12 months prior to the survey, 7.7 % of subjects recalled at least one episode of severe infection requiring admission, and nearly 40 % reported receiving at least one course of antibiotics. Conclusions Infections are common in RA and Rheumatologists need to be adept at recognising at risk patients and managing them appropriately. Influenza vaccination uptake is good whilst pneumococcal vaccination rates are comparatively poor. Collaborative approaches between primary and secondary care are required to maximise vaccine uptake, which is safe and recommended in RA patients.